Tetra- and octa-[4-(2-hydroxyethyl)phenoxy bearing novel metal-free and zinc(II) phthalocyanines: Synthesis, characterization and investigation of photophysicochemical properties - (:unkn) unknown (ELSEVIER, 2015)
In this study, four novel phthalonitriles (1-4) and their corresponding metal-free (5-8) and zinc(II) phthalocyanine derivatives (9-12) bearing 4-(hydroxyethyl)phenoxy groups were synthesized. These novel compounds were characterized by IR, elemental analyses, H-1-NMR, UV-vis, and MALDI-TOF spectral data. Furthermore, photophysical (fluorescence quantum yields and lifetimes) and photochemical properties (singlet oxygen generation and photodegradation quantum yields) of these phthalocyanines were investigated in dimethylsulfoxide. The studied zinc(II) phthalocyanines generated highly singlet oxygen which is very important for the photodynamic therapy (PDT) of cancer. The fluorescence quenching behaviour of the newly synthesized phthalocyanine compounds were also investigated using 1,4-benzoquinone. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Zinc(II); Metal-free; Photochemical; Photophysical; Singlet oxygen; PHOTOCHEMICAL PROPERTIES; PHOTOSENSITIZERS; SUBSTITUENTS; AGGREGATION; WATER